Cardioprotective effect of thiotriazoline in cancer patients - A. V. Koltsov; V. V. Tyrenko (Российский кардиологический журнал)
Aim. To evaluate the effectiveness of morpholinium-methyl-triazolyl-thioacetate (thiotriazoline) as a cardioprotector in patients with non-Hodgkin’s lymphomas who received chemotherapy with the inclusion of anthracyclines.Material and methods. Fifty patients with non-Hodgkin’s lymphomas were examined on the background of antitumor therapy. The patients were divided into 2 following groups: group 1 (n=27) — standard chemotherapy; group 2 (n=23) — thiotriazoline as a cardioprotector. The quality of life was assessed using the SF-36 questionnaire; the level of troponin I and the natriuretic peptide NT-proBNP was determined; an electrocardiography and echocardiography were performed.Results. In the course of the study, significant differences (p<0,05) were found in following parameters: the severity of dyspnea and lower limb edema, alanine aminotransferase, aspartate aminotransferase, creatine phosphokinase, troponin I level, NT-proBNP, corrected QT interval, end systolic volume, left ventricular ejection fraction, E/A ratio. The results obtained indicate the clinical and paraclinical advantage of thiotriazoline and reflect its cardioprotective effect. Conclusion. The use of thiotriazoline makes it possible to prevent and slow down the cardiovascular disease continuum, leading to the development of heart failure or decompensation that exists in this category of patients. Keywords: cardio-oncology, thiotriazoline, heart failure, anthracyclines, cardiotoxicity>˂0,05) were found in following parameters: the severity of dyspnea and lower limb edema, alanine aminotransferase, aspartate aminotransferase, creatine phosphokinase, troponin I level, NT-proBNP, corrected QT interval, end systolic volume, left ventricular ejection fraction, E/A ratio. The results obtained indicate the clinical and paraclinical advantage of thiotriazoline and reflect its cardioprotective effect.Conclusion. The use of thiotriazoline makes it possible to prevent and slow down the cardiovascular disease continuum, leading to the development of heart failure or decompensation that exists in this category of patients.